Electrochemical performance comparison of MWCNTs/Ni (OH)₂ composite materials by two preparation routes - Ortiz, Mariela (2017)
Carbon materials are used to improve the nickel hydroxide electrode capacity in rechargeable alkaline batteries. Herein, we present the preparation of multiwall carbon nanotubes/nickel hydroxide composites (MWCNTs/Ni (OH)₂) by two different routes. The first method consists of the direct incorporation of MWCNTs in the active material, and the second is based on the hydrothermal synthesis of β-nickel hydroxide, where MWCNTs are added to the precursor solutions. The electrochemical properties of the prepared positive electrodes containing MWCNTs/Ni (OH)₂ composites are studied. Electrochemical results indicate that the active material with MWCNTs incorporated before the hydrothermal synthesis is capable of delivering a higher discharge capacity and exhibits a better reversibility than those composites prepared with MWCNTs after the hydrothermal route.